Systematic review of the association between physical activity and burnout - Naczenski, Lea M.; Vries, Juriena D.; Hooff, Madelon L. M.; Kompier, Michiel A. J. (Journal of Occupational Health, 2017)
Abstract: Objective: Burnout constitutes a health risk, and interventions are needed to reduce it. The aim of this study was to synthesize evidence regarding the relationship between physical activity and burnout by conducting a systematic review of longitudinal and intervention studies. Methods: A literature search resulted in the identification of a final set of ten studies: four longitudinal and six intervention studies. In separate analyses for each category, evidence was synthesized by extracting the study characteristics and assessing the methodological quality of each study. The strength of evidence was calculated with the standardized index of convergence (SIC). Results: In longitudinal studies, we found moderately strong evidence (SIC(4)=-1) for a negative relationship between physical activity and the key component of burnout, i.e., exhaustion. We found strong evidence (SIC(6)=-0.86) for the effect of physical activity on reducing exhaustion in intervention studies. As only one study could be classified as a high quality study, these results of previous studies need to be interpreted with some caution. Conclusions: This systematic review suggests that physical activity constitutes an effective medium for the reduction of burnout. Although consistent evidence was found, there is a lack of high quality longitudinal and intervention studies considering the influence of physical activity on burnout. Therefore, future research should be conducted with the aim to produce high quality studies, to develop a full picture of physical activity as a strategy to reduce burnout.